2011
DOI: 10.1002/0471142301.ns0214s57
|View full text |Cite
|
Sign up to set email alerts
|

High‐Speed Multineuron Calcium Imaging Using Nipkow‐Type Confocal Microscopy

Abstract: Conventional confocal and two-photon microscopy scan the field of view sequentially with single-point laser illumination. This raster-scanning method constrains video speeds to tens of frames per second, which are too slow to capture the temporal patterns of fast electrical events initiated by neurons. Nipkow-type spinning-disk confocal microscopy resolves this problem by the use of multiple laser beams. We describe experimental procedures for functional multineuron calcium imaging (fMCI) based on Nipkow-disk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…, various combinations of activated neurons) [24], [34], [35]; however, LFP recordings alone cannot determine whether the dopamine-increased occurrence of SWs reflected an increase in the repetitions of the same SW patterns or an increase in the SW pattern variability. To address this question, we used fMCI, an optical technique that records spikes through action potential-evoked calcium elevations in the cell bodies of the focused neurons [36], because unit activities were not evident in our LFP recordings. A drawback of the fMCI technique is its low time resolution due to slow calcium signal kinetics, so that we could not resolve individual spikes during a SW/ripple event.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, various combinations of activated neurons) [24], [34], [35]; however, LFP recordings alone cannot determine whether the dopamine-increased occurrence of SWs reflected an increase in the repetitions of the same SW patterns or an increase in the SW pattern variability. To address this question, we used fMCI, an optical technique that records spikes through action potential-evoked calcium elevations in the cell bodies of the focused neurons [36], because unit activities were not evident in our LFP recordings. A drawback of the fMCI technique is its low time resolution due to slow calcium signal kinetics, so that we could not resolve individual spikes during a SW/ripple event.…”
Section: Resultsmentioning
confidence: 99%
“…fMCI was conducted using acute slices loaded locally with OGB1-AM [36]. Fluorophores were excited at 488 nm and visualized using a 507-nm long-pass emission filter.…”
Section: Methodsmentioning
confidence: 99%
“…2A). fMCI detects action potentials through action potential-evoked transient calcium elevations in the cell bodies of individual neurons13; simultaneous recording of cell-attached recordings and fMCI from the same cells revealed that spikes were tightly associated with individual somatic ΔF/F transients (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we combined local field potential (LFP) recording with a functional multineuronal calcium imaging (fMCI) technique13 and monitored SW-R-relevant spiking of subicular neuron activity with cellular resolution in acute slices of the mouse hippocampal formation. We unexpectedly found that a fraction of subicular activation occurred before hippocampal SW-R events.…”
mentioning
confidence: 99%
“…Cells in organotypic slices were bulk labeled with OGB-AM1 via glass electrode as described previously (22). Briefly, a 2 mM stock solution of OGB-AM1 in 10% Pluronic F-127/DMSO was diluted in ACSF to a final concentration of 200 mM and loaded into a patch pipette.…”
Section: Fluorescent Probe Labelingmentioning
confidence: 99%